COMBINATION OF OEE AND FMEA METHODS TO ANALYZE THE EFFECTIVENESS OF PRODUCTION MACHINES - Wardhani, Angelia Kusuma; Novareza, Oyong; Purnami, Purnami; Mohamad, Effendi Bin (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Maintenance concepts are required for equipment to maintain effectiveness and quality. One of the maintenance concepts offered is total productive maintenance which connects the synergy between all functions in the organization. In tpm, there is a method to calculate the value of machine effectiveness, namely the overall equipment effectiveness method. The purpose of oee itself is to maximize the output of the results of the available capacity. In this study aims to see the value of the effectiveness of existing machines in the production process. It was found that some OEE values were still below the JIPM level. JIPM itself is the OEE benchmark standard used by the world, jipm explains that the world standard for OEE is 85%.  Therefore, it is necessary to improve the maintenance system by using the TPM pillars of autonomous maintenance and training and education.